The Method of Determination of Heat Emission Characteristics in Piston Self-Ignition Internal Combustion Engine - Ambrozik, Andrzej (Communications - Scientific letters of the University of Zilina, 2005)
The article presents the method of plotting real indicator diagrams for piston internal combustion engines. Owing to the analysis of the diagrams, it is possible to determine the self-ignition delay period and also the characteristics of the relative amount of heat emitted in combustion process. The methodology worked out by the author accounts for changes in the amount and thermodynamic properties of the working medium present in the cylinder.